The emerging role of tissue regulatory T cells in tissue repair and regeneration - Raheem, Abdul; Khan, Ilyas; Ahmad, Iqbal; Wajid, Abdul; Alshahrani, Mohammad Y.; Alzahrani, Fuad M.; Alzahrani, Khalid J.; Qadeer, Abdul; Liao, I-Chuang; Chen, Chien-Chin (Frontiers in Immunology, 2025)
Regulatory T cells (Tregs) are a unique subset of T cells vital for maintaining immune balance, preventing autoimmune diseases, and controlling immune responses. First identified in the early 1990s, Tregs are now well recognized for their role in suppressing excessive immune reactions and promoting tolerance to the body’s tissues. Among the broader Treg population, Tissue regulatory T cells (Tissue Tregs) are distinct as they do more than suppress immunity; they actively contribute to tissue repair and regeneration. Studies in both mice and humans have highlighted the important role of in aiding tissue repair and maintaining tissue integrity. Recent research reveals that Tregs participate in wound healing and tissue regeneration across various organs, including the heart, liver, kidneys, muscles, lungs, bones, and central nervous system. These discoveries emphasize the wide-ranging and significant influence of Tregs in fostering recovery and healing in different tissues throughout the body. These cells are characterized by their ability to produce a variety of growth factors, cytokines, and signaling molecules that support the repair and regeneration of damaged tissues. In this review, we present an overview of the emerging understanding of Treg-mediated repair processes in damaged tissues and organs.